Improving Offline RL by Blending Heuristics - Geng, Sinong; Pacchiano, Aldo; Kolobov, Andrey; Cheng, Ching-An (ICLR 2024, 2024)
We propose Heuristic Blending (HUBL), a simple performance-improving technique for a broad class of offline RL algorithms based on value bootstrapping. HUBL modifies Bellman operators used in these algorithms, partially replacing the bootstrapped values with Monte-Carlo returns as heuristics. For trajectories with higher returns, HUBL relies more on heuristics and less on bootstrapping; otherwise, it leans more heavily on bootstrapping. We show that this idea can be easily implemented by relabeling the offline datasets with adjusted rewards and discount factors, making HUBL readily usable by many existing offline RL implementations. We theoretically prove that HUBL reduces offline RL's complexity and thus improves its finite-sample performance. Furthermore, we empirically demonstrate that HUBL consistently improves the policy quality of four state-of-the-art bootstrapping-based offline RL algorithms (ATAC, CQL, TD3+BC, and IQL), by 9% on average over 27 datasets of the D4RL and Meta-World benchmarks.